posted by Hannah on .
Simplify each expression:
1) (x+8)^2 = x^2 + 64
2) (x-2)^3 = x^3 - 8
3) (x-2y)(x+y) = x^2 - xy -2y^2
4) (x+2)(x^2+3x-2) = x^3 + 5x^2 + 4x-4
Are my answers correct?
Numbers 3) and 4) are correct.
For numbers 1) and 2), you have missed out terms, probably you have not used the right standard formulae.
(a+b)² = a² + 2ab + b²
(a-b)² = a² - 2ab + b²
(a+b)³ = a³ + 3a²b + 3ab² + b³
(a-b)³ = a³ - 3a²b + 3ab² - b³
If you are in an examination where you do not have an easy way to double check the standard formulae, you can treat
(a+b)² = (a+b)(a+b)
which you seem to have no problem solving.
so for (x+8)^2 i would use
a^2 + 2ab + b^2 and a would be 8 but what is b? Would it be 64?